Kinetic properties of tetrameric glycogen phosphorylase b in solution and in the crystalline state. - Leonidas, D. D. (Cold Spring Harbor Laboratory Press, 1992)
R-state monoclinic P2(1) crystals of phosphorylase have been shown to be catalytically active in the presence of an oligosaccharide primer and glucose-1-phosphate in 0.9 M ammonium sulfate, 10 mM beta-glycerophosphate, 0.5 mM EDTA, and 1 mM dithiothreitol, the medium in which the crystals are grown or equilibrated for crystallographic studies (Barford, D. & Johnson, L.N., 1989, Nature 360, 609-616; Barford, D., Hu, S.-H., & Johnson, L.N., 1991, J. Mol. Biol. 218, 233-260). Kinetic data suggest that the activity of crystalline tetrameric phosphorylase is similar to that determined in solution for the enzyme tetramer. However, large differences were found in the maximal velocities for both oligosaccharide or glucose-1-phosphate substrates between the soluble dimeric and crystalline tetrameric enzyme.